THE NEED FOR RESEARCH ON PUBLIC SUBJECTIVE RIGHTSOF PERSONS WITH DISABILITIESFROM THE PERSPECTIVE OF POLISH ADMINISTRATIVE LAW - Sienkiewicz, Tomasz (Review of European and Comparative Law, 2017)
When dealing with citizens, public administration has numerous opportunities for abuse of its privileged position. The study of public subjective rights of disabled persons in public law is important because the relation under administrative law is not an equal relation. The state is always the stronger party. When a party to this relation is a person with a dysfunction of the body, a situation is created which is highly unfavourable for this person because of the natural tendency of the state system (including public authorities) to use its privileged position. This can result in actual discrimination of persons with disabilities. The purpose of the law is the common good and welfare of individual persons. Respecting the welfare of persons with disabilities in the public law guarantees the realization of the common good. One can not create the law while ignoring the rules governing human life. As Petrażycki wrote, “the highest good to which we should strive in policy in general and legal policy in particular – is the moral development of man and the rule of highest rational ethics among human beings, namely, the ideal of love” (Petrażycki, 1968, translation mine).